Predominance of Hydrogen-Utilizing Bacteria Among N2-Fixing Bacteria in Wetland Rice Roots - Watanabe, I.; Barraquio, W.L.; Daroy, Maria Luisa (Canadian Science Publishing, 1982)
Heterotrophic bacteria were isolated from wetland soil, rhizosphere soil, root and basal shoot of wetland rice, dryland soil, and root of dryland rice. The isolates were tested for N2-fixing activity and the ability to grow autotrophically under H2 + CO2 + O2. N2-fixing bacteria capable of autotrophic growth were found almost exclusively from the rhizosphere and the root of wetland rice. In another experiment, all N2-fixing bacteria isolated from wetland rice root had uptake hydrogenase activity. These findings indicate the predominance of hydrogen-utilizing bacteria among N2-fixing bacteria from wetland rice roots.